DUDGEON v. THE UNITED KINGDOM: ANALYZING THE EUROPEAN COURT OF HUMAN RIGHTS FROM A PROCEDURAL PERSPECTIVE - Pitta, Rafael Gomiero; Alves, Fernando de Brito (Argumenta Journal Law, 2022)
This article analyses an important case of the European Court of Human Rights revealing, in addition to its peculiarities from the perspective of human rights, procedural aspects of the European Court, similarities with procedures of domestic jurisdiction of the countries and more relevant procedural acts. In addition, the work shows the evolution of procedures from the time of the trial in 1981 to the present, highlighting the main procedural changes, the justification for them and the impact of the decisions before other human rights courts, especially the Inter-American Court of Human Rights. Using an inductive methodology, the article aimed to describe in detail the Court's procedural functioning through a case study, exposing the main procedural phases and methodologies of judgment adopted by the Court from its establishment to the present. The research, although containing elements of material and international public law, primarily analyses procedural aspects that allow the reader to draw comparatives in the field of procedural law.